The 15-Months Clinical Experience of SARS-CoV-2: A Literature Review of Therapies and Adjuvants - Alessio Danilo Inchingolo; Gianna Dipalma; Angelo Michele Inchingolo; Giuseppina Malcangi; Luigi Santacroce; Maria Teresa D’Oria; Ciro Gargiulo Isacco; Ioana Roxana Bordea; Sebastian Candrea; Antonio Scarano; Benedetta Morandi; Massimo Del Fabbro; et al. (Antioxidants, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus responsible for the coronavirus disease of 2019 (COVID-19) that emerged in December 2019 in Wuhan, China, and rapidly spread worldwide, with a daily increase in confirmed cases and infection-related deaths. The World Health Organization declared a pandemic on the 11th of March 2020. COVID-19 presents flu-like symptoms that become severe in high-risk medically compromised subjects. The aim of this study was to perform an updated overview of the treatments and adjuvant protocols for COVID-19. Methods: A systematic literature search of databases was performed (MEDLINE PubMed, Google Scholar, UpToDate, Embase, and Web of Science) using the keywords: “COVID-19”, “2019-nCoV”, “coronavirus” and “SARS-CoV-2” (date range: 1 January 2019 to 31st October 2020), focused on clinical features and treatments. Results: The main treatments retrieved were antivirals, antimalarials, convalescent plasma, immunomodulators, corticosteroids, anticoagulants, and mesenchymal stem cells. Most of the described treatments may provide benefits to COVID-19 subjects, but no one protocol has definitively proven its efficacy. Conclusions: While many efforts are being spent worldwide in research aimed at identifying early diagnostic methods and evidence-based effective treatments, mass vaccination is thought to be the best option against this disease in the near future.